Asthma and allergy development: contrasting influences of yeasts and other fungal exposures. Issue 1 (January 2015) - Behbod, B.; Sordillo, J. E.; Hoffman, E. B.; Datta, S.; Webb, T. E.; Kwan, D. L.; Kamel, J. A.; Muilenberg, M. L.; Scott, J. A.; Chew, G. L.; Platts‐Mills, T. A. E.; Schwartz, J.; et al.
Summary Background Infancy is a developmental stage with heightened susceptibility to environmental influences on the risk of chronic childhood disease. Few birth cohort studies have detailed measures of fungal diversity data in infants' bedrooms, limiting the potential to measure long‐term associations of these complex exposures with development of asthma or allergy. Objective We evaluated the relation of home fungal levels in infancy to repeated measures of wheeze and development of asthma and rhinitis by age 13, and sensitization by age 12 years. Methods In the Epidemiology of Home Allergens and Asthma prospective birth cohort study, we recruited 408 children with family history of allergic disease or asthma. When children were aged 2–3 months, we measured culturable fungi in bedroom air and dust, and in outdoor air. Main outcomes included ascertainment of symptoms/disease onset by questionnaire from birth through age 13. We estimated hazard ratios and, for wheeze and sensitization, odds ratios for an interquartile increase in log‐transformed fungal concentrations, adjusting for other outcome predictors and potential confounders. Results Elevated levels of yeasts in bedroom floor dust were associated with reduced: i) wheeze at any age; ii) fungal sensitization; and iii) asthma development by age 13 (hazard ratio (HR) = 0.86; 95% confidence interval (CI), [0.75 to 0.98]). Outdoor airborne Cladosporium and dustborne Aspergillus predicted increased rhinitis. Risk of fungal sensitization by age 12, in response to environmental Alternaria and Aspergillus, was elevated in children with a maternal history of fungal sensitization. Conclusions and Clinical Relevance Despite the irritant and allergenic properties of fungi, early‐life elevated dust yeast exposures or their components may be protective against allergy and asthma in children at risk for these outcomes. Ascertainment of fungal components associated with immunoprotective effects may have therapeutic relevance for asthma.